Comparison of four inflation techniques on endotracheal tube cuff pressure using a feline airway simulator. Issue 7 (July 2020) - White, Donna M; Makara, Mariano; Martinez-Taboada, Fernando
Objectives: The aim of this study was to compare four inflation techniques on endotracheal tube cuff (ETC) pressure using a feline airway simulator. Methods: Ten participants used four different endotracheal cuff inflation techniques to inflate the cuff of a low-pressure, high-volume endotracheal tube within a feline airway simulator. The simulator replicated an average-sized feline trachea, intubated with a 4.5 mm endotracheal tube, connected to a circle breathing system and pressure-controlled ventilation with oxygen and medical air. Participants inflated the ETC: by pilot balloon palpation (P); by instilling the minimum occlusive volume (MOV) required for loss of airway leaks during mechanical ventilation; until a passive release of pressure with use of a loss-of-resistance syringe (LOR); and with use of a syringe with a digital pressure reader (D) specifically designed for endotracheal cuff inflation. Intracuff pressure was measured by a manometer obscured to participants. The ideal pressure was considered to be between 20 and 30 cmH2 O. Data were analysed by Shapiro–Wilk, Kruskal–Wallis and χ 2 tests, as appropriate. Results: Participants were eight veterinarians and two veterinary nurses with additional training in anaesthesia. Measured median intracuff pressures for P, MOV, LOR and D, respectively, were 25 cmH2 O (range 4–74 cmH2 O), 41 cmH2 O (range 4–70 cmH2 O), 31 cmH2 O (range 18–64 cmH2 O) and 22 cmH2 O (range 20–30 cmH2 O). D performed significantly better ( P <0.001) than all other techniques, with no difference between the other techniques. Conclusions and relevance: Use of D for cuff inflation achieved optimal cuff pressures. There may be high operator-dependent variability in the cuff pressures achieved with the use of P, MOV or LOR inflation techniques. As such, a cuff manometer is recommended when using any of these techniques.